Ecovisitors economic value in Matang Mangrove Forest Reserve, Perak, Malaysia - Ab Razak, Nurshazwani (2017)
The Matang Mangrove Forest Reserve (MMFR), Taiping, Perak is recognized as having the best management system of mangrove ecosystems globally. It is also rich in biodiversity and is one of the main ecotourism sites in the Taiping district of Perak. MMFR is one of the places developed for the purpose of ecotourism in the National Ecotourism Plan (NEP) 2016-2025 and one of the focus of the NEP is to attract local and international investors to invest in this ecotourism area. However, MMFR's value is still unknown to attract the investors. In addition, this study is to identify the factors that influence the demand for outdoor recreation by ecovisitors in MMFR. Travel Cost Method (TCM) is used to evaluate more users in MMFR as a measure of user satisfaction. This study is also as an estimate of the economic value to ecovisitors at the MMFR. The determination of these values directly represented the actual values of MMFR area in Ringgit Malaysia (RM). Data collection was done using questionnaire for the face-to-face survey session. A total of 396 questionnaires have been used in the analysis. Respondents are comprised of visitors who visit MMFR who are aged between 18 years and above. The questionnaire comprised of five parts, which were administration code, information on the mangrove forest, visit characteristics, trip expenditures and socio-demographic. An Ordinary Least Square Regression (OLS) analysis was conducted to determine the TCM values by using the Statistical Package for Social Science (SPSS). The findings of the OLS analysis showed four (4) variables significantly influencing the number of visits. Consequently, the estimated value of consumer surplus for this study was RM223.19 visit/year. The end result of this study is an estimate the economic value to ecovisitors at the MMFR of RM5 225 324.28 for 2016. From the results of this study, it can help MMFR management to attract local and international investors based on the gross the benefit of the MMFR. In addition, it will help management to further improve the quality of the services and facilities for the benefit of the visitors.